How Video Games Can Become a Tool for Social Policy Criticism: A Study - Arditya Prayogi; Hami, Widodo; Nasrullah, Riki (MID Publisher International, 2024)
Video games are often viewed as part of tertiary activities in human life. As a tertiary activity, video games are then considered to have no function in carrying out meaningful activities in society, including social criticism activities. This article then aims to explain that video games can conceptually and practically be used as a tool for social policy criticism. This article was written using a qualitative descriptive approach supported by a data collection process through literature study. From the results of the study, it is clear that video games are capable of producing and reproducing culture and ideology in people's minds through participatory elements so that they can be created and used as a tool for social criticism of a policy. Conceptually, video games become cultural agents that have their own power in terms of generating open meaning from them. Practically, the form and function of video games as a tool for social criticism has led to the presence of video games as an alternative way of conveying criticism creatively.